Mudi-chood: On the forearm - P Sugathan; Abhay Mani Martin (Wolters Kluwer Medknow Publications, 2011)
Mudi-Chood is a strange dermatosis affecting the nape of the neck and upper back of young women in Kerala State of south India. It was first described by us in 1972. Here we report one more such case recently seen by us.